Numerical simulation of operating characteristics of horizontal filter separators for jet fuel - Zhiliang LEI; Linhui YU; Tian YU; Guilong XU; Qiang SONG; Yuanhua HE (You-qi chuyun)
ObjectiveIn recent years, the rapid growth of China’s civil aviation industry has led to a significant increase in aviation fuel demand, making quality control a top priority. Understanding the operating characteristics of filter separators is crucial for ensuring aviation fuel quality. MethodsOrthogonal tests and numerical simulations were conducted to analyze the velocity difference between the filter separator inlet and the coalescing filter element outlet face, as well as the pressure drop between the separator inlet and outlet, under varying conditions: the number of coalescing filter elements (3, 4, 7), inlet flow rate (98 m3/h, 131 m3/h, 230 m3/h), coalescing filter element permeability (1.74×10−9 m2, 1.74×10−10 m2, 1.74×10−11 m2), and separation filter element permeability (1.82×10−7 m2, 1.82×10−8 m2, 1.82×10−9 m2). The optimal velocity difference scheme was then subjected to inherent frequency analysis to determine whether resonance occurred in the filter elements within the model. ResultsWhen velocity difference served as an evaluation index, a larger difference indicated a more favorable scheme. The inlet flow emerged as the most significant factor affecting the velocity difference, with the optimal scheme identified as A1B3C2D2. This scheme involved the use of seven coalescing filter elements with a permeability of 1.74×10−11 m2, an inlet flow of 230 m3/h, and a separation filter element permeability of 1.82×10−7 m2. When pressure drop served as the evaluation index, a smaller pressure drop correlated with a better scheme. The permeability of coalescing filter elements emerged as the most significant factor affecting the pressure drop, with the optimal scheme identified as A1B1C1D3. This scheme involved the use of seven coalescing filter elements with a permeability of 1.74×10−9 m2, an inlet flow of 98 m3/h, and a separation filter element permeability of 1.82×10−9 m2. Analysis of the inherent frequency characteristics of the optimal scheme, using velocity difference as the evaluation index, revealed that the main frequency of the turbulent fluctuating force between the internal filter elements was lower than the first-order inherent frequency of the filter element. This indicated that the designed structure of the filter separator would not cause resonance that could damage the filter element. ConclusionDuring process design, it is crucial to establish a set of pertinent and systematic theoretical system to guide the design of filter separators with large velocity difference and small pressure drop. The research results can enhance the operating characteristics of horizontal filter separators for jet fuel, extend their service life, and provide a theoretical foundation for optimal design.